STRATEGIC FAMILY WINERY BRAND LAUNCH IN THE VUCA (VOLATILITY, UNCERTAINTY, COMPLEXITY, AMBIGUITY) MARKET: THREE CASE STUDIES FROM SERBIAN MARKET - Paunovic, Ivan; Mamula, Tatjana (Journal of process management and new technologies, 2023)
The purpose of this study is to extend previous research on brand innovation by uncovering the process of family winery branding in relation to the new product launch in the VUCA market on the case of three Serbian wineries. The study deploys qualitative oriented and empirical approach in presenting a multi-case study. Three semi-structured telephone interviews were conducted with owners and/or managers in these three wineries. The results demonstrate that all three family wineries are offering high-end product for the domestic market with smaller one still experimenting with strategic direction of innovating for high-end market while the two larger ones putting focus either on autochthonous grape varieties with eye-cathicng labels or authentic brand identity with strong storytelling. Another important aspect identified is the frugal nature of product launch in the family wineries due to limited resources. The paper presents is among only few studies on new product development in wine business literature.